Progress of local symptoms of superficial vein thrombosis vs. duplex findings - Górski, G; Noszczyk, W; Kostewicz, W; Szopiński, P; Kielar, M; Michalak, J; Marianowska, A; Wilkoswski, D (VASA. Zeitschrift fur Gefasskrankheiten, 2004)
BACKGROUND: Risk of subsequent deep vein thrombosis (DVT) following superficial vein thrombosis (SVT) is not fully appreciated. Mechanisms, time relations and risk factors for DVT arising upon earlier SVT remain unclear. The aim of this study was to analyze time relations between local symptoms of lower limb superficial vein thrombosis, duplex findings and onset of deep vein thrombosis during clinically evident course of SVT. PATIENTS AND METHODS: 46 patients with early (onset less than 72 hours prior to inclusion) clinical diagnosis of SVT, confirmed ultrasonographically were included in this prospective, multicenter study. Progress of pain, erythema and swelling in relation to subsequent ultrasound changes in size and localization of thrombus at 0, 7, 14 and 21 day of study has been recorded. RESULTS: Local symptoms subsided completely during 3 weeks. At that time thrombus disappeared completely only in 26% of cases, in remaining cases decreased in size from average 117.5 mm to 43.0 mm. Thrombus regression was similar to venous blood outflow direction--proximal to femoral area. Thrombus propagation was observed following regression of local symptoms of SVT. 4 cases of DVT (8.7%) were diagnosed at 2-11 days. CONCLUSIONS: Local, clinically detectable symptoms of SVT regress incomparably quicker than thrombus in affected veins. Risk of further thrombus propagation extends well beyond the period of intensive local symptoms of SVT. Regression of thrombus in femoral area requires significantly more time than in popliteal or calf segment. Thrombus propagation is directed with blood flow towards femoral segment.
Keywords: dospělí; Sex Distribution; hodnocení rizik; Female; rozložení podle pohlaví; ultrasonografie; Adult; Venous Thrombosis; ženské pohlaví; lidé; Ultrasonography; Risk Assessment; stupeň závažnosti nemoci; Humans; Risk Factors; Male; progrese nemoci; Aged; Czech Republic; Disease Progression; rizikové faktory; Česká republika; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; Poland; Middle Aged; žilní trombóza; Polsko